2018
DOI: 10.47268/sasi.v24i1.117
|View full text |Cite
|
Sign up to set email alerts
|

Perlindungan Hukum Terhadap Pekerja Anak, Kajian Ketentuan United Nations Convention On The Right Of The Child

Abstract: The State has the duty and role in protecting and guaranteeing the human rights of its citizens. Violations of human rights often occur against vulnerable groups, one of which is children. Children as vulnerable groups have special rights due to their limitations, so they need protection. Countries in the world agree to review the protection of children by signing and ratifying Convention on the Right of the Child 1989. This Convention specifically regulates the protection and guarantee of the rights of the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, de facto, the state has failed to effectively implement the contents and provisions of these ratified laws. This discrepancy is evident through numerous examples of ongoing violations of children's rights, such as the employment of children, despite strong opposition to such practices under international conventions (Tahamata, 2018) This discrepancy highlights a significant gap between the legal obligations of the state and its actual implementation and enforcement. Despite the legal framework being in place to protect minors from engaging in labor, the level of state responsibility in ensuring the protection of children's rights, particularly in preventing child labor, remains relatively low.…”
Section: Legal Framework Of Child Labor Protection In Indonesia After...mentioning
confidence: 99%
“…However, de facto, the state has failed to effectively implement the contents and provisions of these ratified laws. This discrepancy is evident through numerous examples of ongoing violations of children's rights, such as the employment of children, despite strong opposition to such practices under international conventions (Tahamata, 2018) This discrepancy highlights a significant gap between the legal obligations of the state and its actual implementation and enforcement. Despite the legal framework being in place to protect minors from engaging in labor, the level of state responsibility in ensuring the protection of children's rights, particularly in preventing child labor, remains relatively low.…”
Section: Legal Framework Of Child Labor Protection In Indonesia After...mentioning
confidence: 99%
“…Children as vulnerable groups have special rights due to their limitations, so they need protection." (Tahamata, 2018). Islands has not been successful because approaches taken there were not implemented as what was expected, and also the obligations were not completely fulfilled as it was supposed to be (Lestari, & Fachri, 2017).…”
Section: According To Lucia Charlotta Octovinamentioning
confidence: 99%
“…However, in Indonesia, the reverse proof for child labour has not been applied but can only be applied to Limited Liability Company Law, namely to members of the board of directors and commissioners who make mistakes or omissions, in Environmental Law, namely to those responsible for business and/or activities that damage the environment, in the National Consumer Air Transport law, namely to producers who harm consumers and in the case of corruption. Tahamata (2018) in her study that examined legal protection against child labour, showed a result study that the state should be responsible for child labour under the Convention on the Rights of the Child 1989, but the binding force of the rule has not been implemented by the state in accordance with the existing material and conditions. The evidence can be seen from various cases of child rights violations that still occur, such as children who are still employed.…”
Section: Introductionmentioning
confidence: 99%